Relevansi Teologi Kristen Berbasis Keluarga di Era Digital: Pendekatan PAK dalam Membentuk Karakter Siswa - Imania Laia; Sandra Rosiana Tapilaha (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
This study discusses the importance of family-focused Christian theology in building children's character in the digital era through the Christian Religious Education (PAK) approach. The transformation of information and communication technology has brought major changes, including in the fields of education and character formation. The digital era provides opportunities to increase knowledge and access to learning, but also raises challenges in the form of weakening moral values, integrity, and relationships within the family. The family as a divine institution has a primary role in teaching Christian values ​​through role models, communication, and direct experience. This study uses a qualitative method with a descriptive-analytical approach, which reviews literature and observations of Christian education practices both in families and schools. The results show that families have an important role in developing children's faith and character, while PAK serves as a link between faith education at home and formal education at school. PAK is considered relevant because it can unite students' cognitive, affective, and conative aspects in facing the influence of digital culture. Overall, family-based Christian theology supported by PAK has great relevance in shaping a young generation with integrity, critical thinking, and character. This approach not only instills knowledge of faith but also prepares students to become responsible and wise leaders in utilizing technology in accordance with Christian values.